THE IMPLEMENTATION OF SLOW STROKE BACK MASSAGE IN DECREASING BLOOD PRESSURE ON HYPERTENSION’S PATIENT - Prawesti, Dian; Retno, Anastasi Widyo (Jurnal Penelitian STIKES Kediri, 2012)
Hypertension walk slowly and not experienced until someone get significant organ problem. One of nursing interventions is slow stroke back massage. Objective of this research was to analyze the influence slow stroke back massage toward the change of blood pressure on hypertension’s at Puskesmas Pembantu Blabak Wilayah Kerja Puskesmas Pesantren 1 Kota Kediri. Design of this research was pre experiment. Population was the hypertension’s patient. Samples were 24 respondents on purposive sampling. Variable was blood pressure. Data was collected using mercurial sphygmomanometer, for know the influence slow stroke back massage using wilcoxon with significant level α < 0.05. Result of research showed that blood pressures significantly decrease. Slow stroke back massage can decrease blood pressure; with maximal value of systolic were 8.00 mmHg and 24.00 mmHg. Conclusion of this research was there was significant slow stroke back massage toward decreasing of blood pressure, easy to practice, simple using and cheap.